You and me and him - Dinnison, Kris (Houghton Mifflin Harcourt, 2015)
Maggie Bowers thinks she knows what to expect her junior year of high school, but when she and her out-of-the-closet best friend Nash have feelings for the same boy she wonders if winning someone's heart means losing her soulmate.